SUPERSONIC JET GENERATION BY UNDERWATER SUB-MICROSECOND ELECTRICAL EXPLOSIONS OF WIRE ARRAYS - Maler, D.; Krasik, Ya. E.; Efimov, S.; Kozlov, M. (Physics of Plasmas, 2022)
Experiments in which supersonic water jets are generated by underwater sub-𝜇s timescale electrical explosions of cylindrical and conical wire arrays are presented. These are compared with previous experiments [Maler et al., Phys. Plasmas 28, 063509 (2021)] in which the generation of supersonic water jets was demonstrated using a 𝜇s timescale generator. Although in the present experiments less energy is deposited into the wire arrays, the water jets acquire higher velocities compared to when the deposited energy is higher but the timescale is slower. That is, with a higher energy density deposition rate, faster radial wire expansion is induced resulting in a stronger converging shockwave and a faster waterflow behind its front. In addition, two dimensional hydrodynamic numerical simulations show that the formation of the water jet is the result of extremely high pressure at the axis of the shockwave implosion and the cumulative edge effect realized at the array output.
Keywords: Type of access: Open Access; Fluid dynamics; Fluid instabilities; Shock waves; Finite volume methods; Supersonic jets; High energy density physics; Pulse generators; Numerical methods